Systematic review of the perioperative immunotherapy in patients with non-small cell lung cancer: evidence mapping and synthesis - Ni, Yunfeng; Lei, Jie; Huang, Wan; Wang, Jian; Guo, Haihua; Lv, Feng; Kang, Shuhong; Lan, Ke; Jiang, Tao (Frontiers in Oncology, 2023)
Objectives: This study aimed to use evidence mapping to provide an overview of immune checkpoint inhibitors (ICIs) as perioperative treatments for non-small cell lung cancer (NSCLC) and to identify areas of this field where future research is most urgently needed. Methods: Multiple databases (PubMed, EMBASE, Cochrane Library, and Web of Science) were searched to identify clinical trials published up to November 2021 that examined the effect of perioperative ICIs for perioperative treatment of NSCLC. Study design, sample size, patient characteristics, therapeutic regimens, clinical stages, short-term and long-term therapeutic outcomes, surgery associated parameters, and therapeutic safety were examined. Results: We included 66 trials (3564 patients) and used evidence mapping to characterize the available data. For surgery associated outcomes, sixty-two studies (2480 patients) provided complete information regarding the use of surgery after neoadjuvant immunotherapy and data on R0 resection were available in 42 studies (1680 patients); for short-term clinical outcomes, 57 studies (1842 patients) evaluated pathologic complete response (pCR) after neoadjuvant immunotherapy and most of included studies achieved pCR in the range of 30 to 40%; for long-term clinical outcomes, 15 studies (1932 patients) reported DFS, with a median range of 17.9-53.6 months; and only a few studies reported the safety profiles of perioperative immunotherapies. Conclusion: Our evidence mapping systematically summarized the results of all clinical trials and studies that examined ICIs as perioperative treatments for NSCLC. The results indicated more studies that evaluate long-term patient outcomes are needed to provide a stronger foundation for the use of these treatments.